STEM AS A BASIS FOR INNOVATIVE TRAINING OF SPECIALISTS IN THE SYSTEM OF VOCATIONAL EDUCATION (Innovative professional education, 2024)
The role of the STEM field in achieving the Sustainable Development Goals has been updated. The main tasks of STEM education and its possibilities in providing innovative personnel training for high-tech production in the system of vocational education and training are determined. Attention is focused on current STEM trends in professional education and STEM professions. The conditions for the introduction of STEM educationin VET institution are characterized: the operation of STEM centers/laboratories, the use of integrated and project-based learning, the development of STEM-oriented curricula, the involvement of students in scientific and educational activities, the improvement ofthe professional competence of pedagogical workers in the application of STEM technologies, establishing partnerships with stakeholders.
Keywords: education, STEM center/ laboratory, high-tech production, project, digital technologies, research activity, professions, creativity, integration, interdisciplinary approach